(untitled) (Bulletin KNOB, 2013)
The Dutch lowlands consist mainly of polders, areas where water levels are artificially controlled so people can live and work there. This century-old interaction between man and water has produced a rich and of their right polder landscape. The great variety in polder shapes is caused by differences in the geological subsoil, the dynamics of water and land and human intervention. The Dutch lowlands of today are gradually transformed into multifunctional spaces where uses such as leisure and tourism, nature, water storage and housing become more and more important besides agriculture. These developments put pressure on the quality of the space. The key to solving many spatial issues lies in the wealth of shapes of the polder landscape itself. Therefore it is necessary to ‘read’ this landscape correctly in order to retrieve the information and design knowledge that lies hidden within it and then apply them in the right way. De polderkaart van Nederland (The Polder Map of the Netherlands) systematically visualises the wealth in shapes of the polder landscape. Polders are not just regarded as hydraulic phenomena but also as spatial constructions: the polder landscape as we can see and experience it. This combination provides us with clues to steer developments in the right direction and guarantee their spatial quality. The map focuses on the polder as both an hydraulic and spatial landscape unity, revealing its cohesion through systematic analysis and cartography. The use of Geographic Information Systems (GIS) not only ensures precision work, but also makes it possible to link information to the map, turning it into a spatial database. The spatial shape is derived from the combination of the Hydraulic Map first edition 1865-1891 and the Topographic and Military Map 1850-1864 (TMK), supplemented with all land reclaimed after 1850. The map shows all water level management areas and hydraulic polders in the lower parts of the Netherlands together with their specific boundaries. Within this framework, the polders are designated as spatial units. Also, based on the Geographical Dictionary of the Netherlands (Van der Aa, 1939-1851), a database was created with all the polders that are mentioned in this dictionary. This information makes it possible to supplement and check the data from the TMK and Hydraulic Map. By applying GIS the information can become spatial and available for analysis. The map provides both an overview and a ‘benchmark’, a point of reference from which the history of the polder landscape can be reconstructed and that provides a perspective of the present and the future. This article provides a brief outline and a state of affairs of the research in connection with the polder map. It also describes hitherto unpublished backgrounds and places the map within the context of development-oriented landscape research. The article demonstrates how the connection between hydraulic and landscape-spatial aspects of the Dutch polder landscape may be mapped, and that the polder map can be an instrument in the spatial research and development of the polder landscape.